Learning from Power Sector Reform Experiences : The Case of Kenya - Godinho, Catrina (World Bank, Washington, DC, 2019)
Two successive waves of reform have fundamentally altered the structure and organization of Kenya's vibrant power sector, which boasts a tradition of strong technical and commercial performance. In the first wave -- beginning in 1996 and largely donor-driven -- policy and regulatory functions were separated from commercial activities; generation was unbundled from transmission and distribution; cost-reflective tariffs were introduced; and generation was liberalized. In the second wave -- beginning in 2002 and led by domestic reform champions -- the thrust of first-wave reforms was continued, with the strengthening of independent regulation, partial privatization of the generation company (KenGen), and establishment of complementary entities. Although the government retains majority ownership of the largest power utilities in the country (Kenya Power, ~51 percent; KenGen, ~70 percent), Kenya has been able to position itself as one of the foremost destinations in the region for private energy investment. The reforms have improved the operational efficiency of the sector, increased cost recovery, and captured a significant amount of private sector investment. At the same time, the state has remained an important investor, playing a pivotal role in expanding generation capacity, scaling up electrification at an exceptionally rapid pace, and leading diversification toward geothermal energy. Political influence in sector decisions remains significant, in planning and tariff reviews.